VIBRATION ANALYSIS OF LOW-ASPECT RATIO ROTATING BLADE MODELED AS A PLATE - Alaemayehu, Benyam; Bazezew, Alem (Zede Journal of Ethiopian Engineers and Architects, 2023)
Vibration analysis of a low-aspect ratio blade modeled as a plate is presented which uses MATLAB coded computer program The analysis presented employs an accurate strain-displacement relationship based on the thin plate theory, known as the Kirchhoff - Lava hypothesis. The equation of motion of the blade is derived using Kirchhoff Lava plate theory, and the problem is solved by the finite element method, where rectangular plate elements with four nodes and three degrees of freedom for each node are utilized. A computer simulation of a numerical example is given to show the vibration characteristics of the rotating blade. Natural frequencies, corresponding mode shapes and the free vibration response are determined. Induced stresses related to the mode shapes are computed., and nature of these stresses are compared to actual datafrom the aviation industry.